Hearing damage from exposure to music - JAROSZEWSKI, A.; FIDECKI, T.; ROGOWSKI, P. (Archives of Acoustics, 1998)
Sound pressure levels and exposures in discotheques and youth clubs and during training sessions of music students were measured and analysed. Effects of exposure in the form of permanent and temporary threshold shift were determined in the samples of young discotheque attendants and in music students. The consequences of the threshold shift in the perception of pitch, loudness, and time are discussed.